Diding Musuh Suka Arrangements Tipan Sembiring Works - Ranita Br. Sitepu; Hendrik L. Simanjuntak; Kartini R.M. Manalu (Jurnal Ilmu Sosial Mamangan, 2023)
Tipan Sembiring was a Karo artist, but he was better known as a perkolong-kolong (Karo singer) around 1930-1970. Tipan Sembiring is also one of the women's groups who compose songs with quite poetic lyrics. This research aims to arrange musical arrangements for the diding enemy like the work of Tipan Sembiring. The method approach used to identify the study of the arrangement of the song Diding Musuh Suka by Tipang Sembiring is qualitative research. As for changes within the song, namely those resulting from the accumulated creative efforts of individuals or groups; and there is a change in the entire structure of tradition, as a result of internal or external pressures. The song Diding Musuh Suka by Tipan Sembiring has an interesting history related to the agreement between two singers which culminated in Tipan Sembiring's marriage to Sayang Barus, in 1937. The musical composition of this song still uses traditional musical instruments and has no variations or modulations. Even though it is said that the production was 'simple', it still took into consideration musical elements such as; tempo, rhythm, dynamics, melody, and intro. The Karo singing style is part of what is put forward as a form of cultural richness that cannot be separated from where musical activity grows and develops. The method of transcribing the song Diding Musuh Suka shows how Tipan Sembiring composed his work by prioritizing musical experience. Of course, the composition of the work is more 'tinged' with Karo culture by accommodating the Western music system